God Hidden in the Faith Experience of Blessed Honorat Koźmiński - Synowczyk OFMCap, Kazimierz (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
In Father Honorat's theological reflection and personal experience of faith, the category of hidden God occupies a special place. It is about contemplating the life of the Holy Trinity, which is in fact unfathomable and hidden from human knowledge. The Blessed One first discovers God the Creator, who, being the Lord of the universe, is hidden in his work of creation. Koźmiński also sees the hiddenness of God in the mystery of the incarnation of the eternal Word and in the sanctifying action of the Holy Spirit. The continuation of the Incarnation is the Church of Christ. In Him, too, and in a unique way, God remains hidden in the Holy Eucharist.